2018
DOI: 10.1016/j.clbc.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Study of Dose-Dense Doxorubicin and Cyclophosphamide Followed by Eribulin Mesylate With or Without Prophylactic Growth Factor for Adjuvant Treatment of Early-Stage Human Epidermal Growth Factor Receptor 2–Negative Breast Cancer

Abstract: The primary end point of > 80% feasibility was not met. No unexpected adverse events were observed, and 62% of patients received full dosing with no dose delay or reduction. Further investigation of this regimen with alternative dosing schedules or use of growth factors could be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In this study, the combination of carboplatin and eribulin produced a pCR rate of 43%, with mostly grade 1 and 2 toxic effects [6]. Cadoo et al conducted a phase II trial of the feasibility (defined as the percentage of patients who completed the regimen) of dose‐dense doxorubicin/cyclophosphamide (AC) followed by eribulin with and without prophylactic filgrastim in patients with stage I–III, HER2‐nonamplified early‐stage breast cancer, and showed that eribulin along with AC combination in neoadjuvant therapy for stage I–III patients was feasible in only 72.9% when pegfilgrastim was used and in only 60% when pegfilgrastim was not used [7]. This is in line with the toxicity that was observed in our study.…”
mentioning
confidence: 99%
“…In this study, the combination of carboplatin and eribulin produced a pCR rate of 43%, with mostly grade 1 and 2 toxic effects [6]. Cadoo et al conducted a phase II trial of the feasibility (defined as the percentage of patients who completed the regimen) of dose‐dense doxorubicin/cyclophosphamide (AC) followed by eribulin with and without prophylactic filgrastim in patients with stage I–III, HER2‐nonamplified early‐stage breast cancer, and showed that eribulin along with AC combination in neoadjuvant therapy for stage I–III patients was feasible in only 72.9% when pegfilgrastim was used and in only 60% when pegfilgrastim was not used [7]. This is in line with the toxicity that was observed in our study.…”
mentioning
confidence: 99%
“…Possible causes of the difference in the results of pre-operative eribulin treatment for early breast cancer and those of eribulin treatment for metastatic breast cancer include the following factors. First, eribulin has different modes of action: one is a blockade of cell cycle progression by inhibition of microtubule growth, and the other is non-mitotic complex effects on tumor biology, including induction of vascular remodeling, suppression of cancer cell migration and invasion, and reversal of the epithelial-tomesenchymal transition (13)(14)(15)(16)(17)(18)(19). Short-term exposure to eribulin of a bulky mass with stage III would not be enough to improve the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, significant anticancer activity is seen in ER, PgR and HER2 negative metastatic BC cases [10]. So far few studies evaluating E in localized BC either in combination with carboplatin [27], and trastuzumab [28], or as monotherapy [29] after anthracycline-based chemotherapy have been reported. Overall, results showed that E has a favorable peripheral neuropathy toxicity profile, without any clearly improved activity over historical results with standard treatment with paclitaxel [28].…”
Section: Discussionmentioning
confidence: 99%